2023
DOI: 10.1051/cagri/2022031
|View full text |Cite
|
Sign up to set email alerts
|

Visions contrastées des services écosystémiques des zones humides saisonnières du Gharb, Maroc

Abstract: Immergés en hiver, les marais saisonniers (merjas) de la plaine du Gharb au Maroc étaient traditionnellement exploités pour le pâturage en été, à côté d’autres usages productifs. Pourtant, ils étaient considérés par l’administration coloniale comme des milieux insalubres et peu valorisés, malgré leur abondance en ressources naturelles. Au cours du XXe siècle, la plaine a fait l’objet d’un aménagement hydro-agricole, incorporant les merjas, pour contribuer aux objectifs nationaux de sécurité alimentaire et d’ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…1). The extent of surface water in the central merjas varies seasonally from inundated to dry (Choukrani et al, 2023), making their dynamics difficult to manage and inviting different interpretations of the landscape where the borders between land and water are fluid and at times imperceptible. Together, they cover an area of about 20,000 ha, although clearly demarcating them is challenging.…”
Section: Description Of the Study Sitementioning
confidence: 99%
See 4 more Smart Citations
“…1). The extent of surface water in the central merjas varies seasonally from inundated to dry (Choukrani et al, 2023), making their dynamics difficult to manage and inviting different interpretations of the landscape where the borders between land and water are fluid and at times imperceptible. Together, they cover an area of about 20,000 ha, although clearly demarcating them is challenging.…”
Section: Description Of the Study Sitementioning
confidence: 99%
“…On the one hand, they are part of the projected 250,000 ha Gharb irrigation scheme, constituting a land reserve for further State-led reclamation and the further development of irrigation schemes. On the other hand, feasibility studies have revealed the difficulties (topography, heavy clayey and hydromorphic soils) and the cost of land development in these low-lying areas (Choukrani et al, 2023).…”
Section: Different Ontologies Of Merjas Different Enactmentsmentioning
confidence: 99%
See 3 more Smart Citations